1984
DOI: 10.1007/bf00383522
|View full text |Cite
|
Sign up to set email alerts
|

A physical map of bacteriophage T4 including the positions of strong promoters and terminators recognized in vitro

Abstract: We present a linearized physical map of the genome of bacteriophage T4. This map contains the cleavage sites for restriction enzymes SmaI, KpnI, SalI, BglII, XhoI, XbaI, ClaI , HaeII, EcoRI, and EcoRV . It also contains about 200 TaqI sites. The promoter sites recognized in vitro and a number of rho independent terminators have also been mapped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…2, 3 promoter (39,46). Hilfinger, using Northern blot analysis with probes from segments of either nrdA or nrdB, has found that mRNA from phage-infected cultures reached sizes of about 6 kb (unpublished data), supporting our previous findings (46), those of Gram et al (25), and those of Ruckman and co-workers (42). That the frd and td genes overlap slightly (14,40) and that the translational frames of nrdB and denA are separated by only 30 bp (43) argue against promoters in these interfaces.…”
Section: Discussionsupporting
confidence: 88%
“…2, 3 promoter (39,46). Hilfinger, using Northern blot analysis with probes from segments of either nrdA or nrdB, has found that mRNA from phage-infected cultures reached sizes of about 6 kb (unpublished data), supporting our previous findings (46), those of Gram et al (25), and those of Ruckman and co-workers (42). That the frd and td genes overlap slightly (14,40) and that the translational frames of nrdB and denA are separated by only 30 bp (43) argue against promoters in these interfaces.…”
Section: Discussionsupporting
confidence: 88%
“…amN55 x 5 resulted from a G + A exchange in a TGG codon (Trp) and amC87 from a C + T exchange in a CAG codon (Gln). The transcription of gene 42 apparently can be started from the early promoter, as already shown under in vitro conditions [34]. The early mode of transcription includes the imm gene.…”
Section: Open Readingjrumes Transcription and Translation Signalsmentioning
confidence: 55%
“…The expression of pinA in the Q43 and L512 lysogens is probably different from that which occurs during T4 infection. First, three strong promoters, approximately 4, 7, and 9 kb upstream of pinA, are recognized in vitro by unmodified RNA polymerase (15). Although a termination sequence may be present between these promoters and the early promoter immediately upstream of pinA (J. Tomaschewski and W. Ruger, unpublished data), its effects on transcription in vivo are unknown.…”
Section: Resultsmentioning
confidence: 99%